SUPPLY CHAIN MANAGEMENT INFORMATION SYSTEM IN RESTAURANT BUSINESS: ANALYSIS AND CASE STUDY IN PANGKEP REGENCY SOUTH SULAWESI - Wiwiek Hidayati; Megawati, Megawati; Wahyuni Zam; Seniorita Seniorita (ZILLZELL MEDIA PRIMA, 2025)
Supply Chain Management (SCM) has evolved into a fundamental element of modern business strategy, extending beyond the manufacturing sector to encompass the service and retail industries. SCM involves the application of management science and practice throughout the supply chain, aimed at achieving competitive advantage amid intense industry competition. In an increasingly digitalized business landscape, SCM is no longer focused solely on the physical movement of products and financial flows. This study aims to analyze and understand the life experiences of owners and managers of micro, small, and medium enterprises (MSMEs) restaurants in Pangkep Regency related to supply chain management and adopting supply chain management information systems (SCMIS). The background of the study reveals a gap between the 'Sollen' of efficient SCMIS and the 'Sein' of MSME restaurants, which still face various operational and financial challenges due to limited technology and manual processes. This study identifies the need for an in-depth understanding of the challenges and opportunities for adopting SCMIS from the subjective perspective of MSME actors. This study used a qualitative approach, descriptive phenomenological design, and Interpretative Phenomenological Analysis (IPA) data analysis with Saldana coding techniques supported by NVivo software; this study involved 20 informants from MSME restaurants in Pangkep Regency. The research findings present themes that emerge from the informants' experiences and are visualized in a flow relationship framework. The main contribution of this study lies in providing a rich and nuanced understanding of the dynamics of technology adoption in the context of MSME restaurants, which can be the basis for practical recommendations and the development of more relevant policies.